Peran Kelompok Tani Taruna Permata Hijau Dalam Pemberdayaan Masyarakat Melalui Pembenihan Tanaman Kunyit Di Desa Bontolempangan Kabupaten Kepulauan Selayar - Andi Tenri Ani; Muliaty Amin; Nur Laelah Abbas (Jurnal Berita Sosial, 2024)
The main problem of this research is the role of the Taruna Permata Hijau Farmer Group in community empowerment through Turmeric Plant Seeding in Bontolempangan Village, Buki District, Selayar Islands Regency. The main problem is further described into several sub-problems, namely: 1) What is the role of the Taruna Permata Hijau Farmer Group in empowering the community through turmeric plant hatcheries in Bontolempangan Village, Buki District, Selayar Islands Regency, 2) What are the obstacles experienced by the Taruna Permata Hijau Farmer Group in empowering the community in Bontolempangan Village, Buki District, Kep. Selayar Regency. This type of research is qualitative research using a sociological approach. The data sources in this research are administrators and members of the Taruna Permata Hijau Farmer Group, as well as the Turmeric Farming Community of Bontolempangan Village. The data collection methods used are observation, interviews, and documentation, using data analysis in the form of data reduction, data presentation, and conclusion drawing. The results of the study illustrate that 1) The role of the Taruna Permata Hijau Farmer Group in Community Empowerment through Turmeric Plant Seeding in Bontolempangan Village, Buki District, Selayar Islands Regency, namely: a) As a Learning Class, b) As a Cooperation Vehicle, c) As a Production Unit. 2) The obstacles experienced by the Taruna Permata Hijau Farmer Group in the community empowerment process are caused by several factors, namely: a) difficult road access, b) inadequate human resources, c) lack of articles of association (AD/ART) which is the foundation of the organization, d) lack of agricultural tools.